Joint utterance construction in Japanese conversation - Hayashi, Makoto (Studies in discourse and grammar ;, 2003)
This book focuses on how participants in Japanese conversation negotiate and achieve joint courses of action within a single turn at talk. Using the methodology of Conversation Analysis as a central framework, this book describes in detail the structures and procedures used by Japanese speakers to jointly produce a coherent grammatical unit-in-progress, and explores the range of social actions that speakers accomplish by employing that practice. This study is part of a larger project intended to investigate how humans achieve intricate coordination of their behavior with that of co-participant.